Relationship Between Problematic Social Media Usage and Employee Depression: A Moderated Mediation Model of Mindfulness and Fear of COVID-19 - Majeed, Mehwish; Irshad, Muhammad; Fatima, Tasneem; Khan, Jabran; Hassan, Muhammad Mubbashar (Frontiers in Psychology, 2020)
Social media's significant role in modern life cannot be denied, but its excessive use during COVID-19 has become a source of concern. Supported by the conservation of resources theory, the current study extends the limited literature on problematic social media usage during COVID-19 by investigating its association with emotional and mental health outcomes. In a moderated mediation model, this study proposes that problematic social media use by workers during COVID-19 is linked to fear of COVID-19, which is further associated with depression. The current study tested trait mindfulness as an important personal resource that may be associated with reduced fear of COVID-19 despite problematic social media use. The study collected temporally separate data to avoid common method bias. Pakistani employees (N=267) working in different organizations completed a series of survey questionnaires. The results supported the moderated mediation model, showing that problematic social media use during the current pandemic is linked to fear of COVID-19 and depression among employees. Furthermore, trait mindfulness was found to be an important buffer, reducing the negative indirect association between problematic social media use and depression through fear of COVID-19. These results offer implications for practitioners. The limitations and future research directions are also provided.